Dynamic Range Improvement for an Analog Photonic Link Using an Integrated Electro-Optic Dual-Polarization Modulator - Zihang Zhu; Shanghong Zhao; Xuan Li; Kun Qu; Tao Lin; Baoqin Lin (IEEE Photonics Journal, 2016)
A novel analog photonic link with enhanced spurious-free dynamic range (SFDR) based on an integrated electro-optic dual-polarization modulator is presented and demonstrated. The dual-polarization modulator, which consists of a polarization beam splitter, a polarization beam combiner, and two $z$ -cut LiNbO3 MZMs, can achieve complementary intensity modulation along the orthogonal polarization directions with different modulation indexes. By properly adjusting the power relationship of the orthogonal polarization directions, two third-order intermodulation distortions (IMD3) have equal intensity and opposite phase and cancel each other out. Combined with a low-biasing technique to reduce the noise power, the SFDR of the link can be further improved. A theoretical analysis is presented and validated by a simulation. The IMD3 can be suppressed by 30.6 dB, giving an improvement in SFDR of about 22 dB compared with a conventional optical double-sideband modulation link.